PENGARUH BOPO TERHADAP ROE PADA PT. BANK NEGARA INDONESIA,TBK - Uswatun Hasanah; Muniarty, Puji (Journal of Student Research, 2024)
This research aims to determine and analyze the significant influence of BOPO on ROE at PT. Bank Negara Indonesia, Tbk. This research is associative type using secondary data. The research instrument used is a list of tables containing data on operational expenses, operating income, net profit and total equity at PT. Bank Negara Indonesia, Tbk for 10 years, namely from 2013 to 2022. The population in this research is all financial reports of PT. Bank Negara Indonesia, Tbk has been listed on the IDX from 1996 to 2022, which is 26 years. The sample in this research is the financial report of PT. Bank Negara Indonesia, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling. Data collection techniques use documentation and literature study. The data analysis technique in this research is to use component analysis of the ratio of BOPO (X) to ROE (Y) and statistical analysis consisting of simple linear regression analysis, simple correlation coefficient, determination test and t test. The research results show that there is a significant influence of Operational Costs on Operational Income (BOPO) on Return On Equity (ROE) at PT. Bank Negara Indonesia, Tbk with a strong level of relationship.